Peran Keputusan Pembelian dalam Memediasi Pengaruh Brand Image, Social Media Marketing, dan Lifestyle terhadap Kepuasan Pelanggan Sepatu Adidas - Rahadatul Aisy Syafa Q.A; Vincent Didiek Wiet Aryanto; Ariati Anomsari; Linda Ayu Oktoriza; Elia Resha Fatmawati (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to investigate how brand image, social media marketing, and lifestyle affect Semarang City consumers' satisfaction with Adidas sneakers. For a survey with a quantitative approach, 100 respondents were chosen via purposeful sampling. The data was analyzed using SmartPLS 4.0 and partial least squares structural equation modeling (PLS-SEM). The results demonstrate that social media marketing, lifestyle, and brand image have a favorable and significant impact on consumer satisfaction and purchasing decisions. Furthermore, consumer pleasure is positively and significantly impacted by purchasing decisions, which mediate the relationships between brand image, social media marketing, lifestyle, and customer contentment. These results imply that improving social media marketing, enhancing company image, and matching items to consumers' lifestyles will improve customer happiness and purchase decisions. Adidas should therefore keep improving its product positioning and marketing tactics in order to sustain consumer satisfaction and competitiveness.